Analisis Sentimen Persepsi Masyarakat Terhadap Timnas Indonesia U-23 dalam AFC-23 Asian Cup 2024 Pada Media Sosial X Menggunakan Metode Naïve Bayes Classifier - Nufus, Reda Hayati; Surapati, Untung (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Social media Twitter, or now called X, not only serves as an effective communicative medium, but it can also make it easier for people to find information or interact directly with other X users, and become a container for holding opinions. X users in Indonesia often express their opinions on all areas including sports, especially the Indonesian Football Team, which has recently been heatedly discussed because of the talent of all the players who succeeded in attracting the attention not only of football fans, but of the entire Indonesia public at the AFC ASIA CUP U 23 2024 competition held in the country of Qatar. The study uses the Naive Baiyes classification method to analyze the sentiment of comments and comments on Social Media X against each match. Sentiment data from user comments on social media X is collected and classified as positive, and negative. The final results of sentimental analysis using the naïve bayes method showed accuracy values of 73.94% out of 972 datasets, with 143 predicted negative data and 828 predictable positive data. So it can be concluded that most of the public's perception is positive because they see the struggle and performance of the Indonesian National Football Team in making the nation proud.